Apotek Hidup sebagai Alternatif Pemanfaatan Lahan Kosong di Desa Pringgarata Kabupaten Lombok Tengah - Qarina Annis Syamila; Taufiq Ramdani; Lalu Farid Auliya Rahman (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
A living pharmacy is an activity of land use in growing medicinal plants. Empty land if left abandoned can reduce the value of its beauty. Therefore, the vacant land can be used as a living pharmacy. So in this study, the use of vacant land as a living pharmacy was carried out with the aim of providing knowledge and making living pharmacies on vacant land at the Pringgarata Village office. The methods used in this research are socialization and the manufacture of a live pharmacy. The result of this study is the realization of a live pharmacy in the Pringgarata village office yard. It is hoped that this activity can provide knowledge, produce herbal plants that can be used by the community and can be imitated for the use of vacant land in the residents' yards.